Apropriação e ritmanálise dos parques urbanos pelas práticas de lazer: análise comparativa do Parque Marcos Veiga Jardim - Goiânia - GO e do Parque Madureira Mestre Monarco - Rio de Janeiro - RJ - Sousa, Flávia Kênia de Jesus (2025)
This thesis is the result of a research that has examined the rhythm at which citizens currently use, consume, appropriate, and present themselves in urban parks through leisure practices. The methodological foundation of the investigation is a comparative analysis between Marcos Veiga Jardim Park – Goiânia, GO (PMVJ), located in an elite neighborhood, and Madureira Mestre Monarco Park – Rio de Janeiro, RJ (PMMM), situated in the suburbs of Rio de Janeiro. The study employed mixed methods, combining qualitative and quantitative elements, as it considered both measurable data, in explanatory terms, and non-measurable data, in descriptive-comprehensive terms. To achieve this, bibliographic, documental, and rhythmanalytic surveys were conducted, specifically utilizing Lefebvrian Rhythmanalysis at all stages of the research. Interviews with park users were also conducted, featuring both objective and discursive questions to, among other objectives, identify the profile and status of visitors' self-presentation; understand the meanings and perceptions they associate with the parks and how they present themselves in these public spaces; highlight the contradictions between the rhythms of these spaces and those of urban everyday life as a whole; investigate the daily and seasonal rhythmic variations in park appropriations and certain "natural" aspects; assess the benefits, expectations, and demands for these spaces; and question the perspectives and potentialities given by patrimonialization. It is stated that the main concepts worked on in the thesis are rhythms, daily life, urban parks, leisure and heritage, which are clarified based on other complementary concepts, such as citizenship, public space and clothing. The comparative analysis, based on the rhythm analysis of two parks, resulted in significant scientific advances by examining the differences and similarities in the social, cultural and environmental rhythms that define these spaces, as well as in their patrimonialization. Rhythmanalysis, proposed as the central method of this study, sought to understand how rhythms manifest themselves in different contexts and how they influence the experience of space-time. It proved to be extremely relevant for understanding rhythms in the comparison between Marcos Veiga Jardim Park and Madureira Mestre Monarco Park. Thus, it becomes a valuable tool for investigating other rhythms of life in future research.